Comparison of Internal Audit Disclosure in Islamic and Conventional Banks in Indonesia - Aziza, Nur Amalia (Review on Islamic Accounting, 2025)
This study aims to assess the disclosure practices in internal auditing within Islamic and conventional contexts, recognizing the vital role of internal audit functions in ensuring governance and managing risks, particularly in the banking sector. The research employs a qualitative methodology, conducting content analysis on 40 annual reports from Islamic and conventional banks in 2022-2023 to evaluate the extent of disclosure, which serves as a proxy for internal audit quality. The sample selection involved 10 Islamic banks and 10 conventional banks, chosen through purposive sampling. The findings reveal that despite the expectation for Islamic banks to prioritize full disclosure, they still fall short compared to conventional banks. Larger banks demonstrate higher transparency levels in information disclosure than medium and small banks. Additionally, conventional banks tend to offer more transparency than Islamic banks, emphasizing not only risk management but also value enhancement through consulting services. In contrast, Islamic banks place greater emphasis on regulatory compliance, with only a minority leveraging internal audits for advisory purposes. This research highlights the need for Islamic banks in Indonesia to enhance their transparency levels in internal auditing processes to improve overall governance and risk management effectiveness.